PERAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN KUALITAS AUDIT - Asmaul Husna (HUMAN FALAH: Jurnal Ekonomi Dan Bisnis Islam, 2024)
Audit quality is a major concern for various stakeholders. Along with the development of information technology, there is hope that technology can be a solution to improve audit quality. This study will specifically analyze the application of technologies such as data analytics, artificial intelligence, and cloud computing in the audit process. Through case studies at several public accounting firms, the research will identify the impact of technology use on testing efficiency, audit result accuracy, and reporting quality. Additionally, the study will examine the challenges auditors face in adopting new technologies, as well as the associated ethical implications.